Interfacial S–O bonds specifically boost Z-scheme charge separation in a CuInS2/In2O3 heterojunction for efficient photocatalytic activity. Issue 12 (13th March 2023) - Fu, Xiaofei; Tao, Junwu; Zhao, Zizhou; Sun, Siwen; Zhao, Lin; He, Zuming; Gao, Yong; Xia, Yongmei
Abstract : Schematic representation of the proposed photocatalytic mechanism on CuInS2 /In2 O3 for LOM degradation and Cr(vi ) reduction under visible light irradiation. Abstract : Reducing the recombination rate of photoexcited electron–hole pairs is always a great challenging work for the photocatalytic technique. In response to this issue, herein, a novel Z-scheme CuInS2 /In2 O3 with interfacial S–O linkages was synthesized by a hydrothermal and subsequently annealing method. The Fourier transform infrared (FT-IR) and X-ray photoelectron spectrometer (XPS) measurements confirmed the formation of covalent S–O bonds between CuInS2 and In2 O3 . The quenching and electron spin resonance (ESR) tests revealed the Z-scheme transfer route of photogenerated carriers over the CuInS2 /In2 O3 heterojunctions, which was further verified theoretically via density functional theory (DFT) calculations. As expected, the CuInS2 /In2 O3 heterojunctions showed significantly boosted photocatalytic activities for lomefloxacin degradation and Cr(vi ) reduction under visible light illumination compared with the bare materials. Accordingly, a synergistic photocatalytic mechanism of Z-scheme heterostructures and interfacial S–O bonding was proposed, in which the S–O linkage could act as a specific bridge to modify the Z-scheme manner for accelerating the interfacial charge transmission. Furthermore, the CuInS2 /In2 O3 heterojunction also exhibited excellent performance perceived in the stability and reusability tests. This work provides a new approach for designing and fabricating novel Z-scheme heterostructures with a high-efficiency charge transfer route.